Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study. - Zhu, Jia-De; Yang, Li-Juan; Zhao, Jian-Nan; Wang, Ping; Li, Yi-Hua; Zhang, Xue-Sha; Pan, Jian-Mei; Jiang, Meng-Han; Yang, Hai-Ying; Yin, Sun-Jun; He, Gong-Hao (European Journal of Clinical Pharmacology, 2024)
Purpose: Previous studies showed that long-term use of proton pump inhibitors (PPIs) was associated with cardiovascular events. However, the impact of short-term PPI exposure on intensive care unit (ICU) patients with myocardial infarction (MI) remains largely unknown. This study aims to determine the precise correlation between short-term PPI usage during hospitalization and prognostic outcomes of ICU-admitted MI patients using Medical Information Mart for Intensive Care IV database (MIMIC-IV). Methods: Propensity score matching (PSM) was applied to adjust confounding factors. The primary study outcome was rehospitalization with mortality and length of stay as secondary outcomes. Binary logistic, multivariable Cox, and linear regression analyses were employed to estimate the impact of short-term PPI exposure on ICU-admitted MI patients. Results: A total of 7249 patients were included, involving 3628 PPI users and 3621 non-PPI users. After PSM, 2687 pairs of patients were matched. The results demonstrated a significant association between PPI exposure and increased risk of rehospitalization for MI in both univariate and multivariate [odds ratio (OR) = 1.157, 95% confidence interval (CI) 1.020–1.313] analyses through logistic regression after PSM. Furthermore, this risk was also observed in patients using PPIs > 7 days, despite decreased risk of all-cause mortality among these patients. It was also found that pantoprazole increased the risk of rehospitalization, whereas omeprazole did not. Conclusion: Short-term PPI usage during hospitalization was still associated with higher risk of rehospitalization for MI in ICU-admitted MI patients. Furthermore, omeprazole might be superior to pantoprazole regarding the risk of rehospitalization in ICU-admitted MI patients.